New insights into synergistic effects and active species toward Hg0 emission control by Fe(VI) absorbent. (15th January 2015) - Han, Yinghui; Fan, Maohong; Russell, Armistead G.
Graphical abstract: Highlights: Fe(VI) is a promising agent for Hg 0 control. Removal of Hg 0 was optimized with the response surface methodology. Synergic effect of pH and temperature is considerable. Species analysis and thermodynamics revealed Hg 0 removal mechanism. Abstract: With the timelines for implementation of the U.S. Environmental Protection Agency's mercury emission control rules approaching soon, finding an innovative and cost-effective mercury removal technology has become increasingly important. The most challenging species in all the mercury forms is gaseous elemental mercury (Hg 0 ). The objective of this work is to inspect the absorption behavior and removal of Hg 0 by Fe(VI). The synergistic effects of various factors were investigated and the optimization for Hg 0 removal by Fe(VI) was achieved based on the response surface methodology. The speciation of Fe(VI) and Hg reaction species was emphatically analyzed in the entire pH range in order to clarify the possible Fe(VI)-based Hg 0 removal mechanism in depth. According to the thermodynamics calculation, the Gibbs free energies for the reaction between Fe(VI) and Hg 0 in the weak alkaline/acid medium are determined as −120.03 kJ/mol and −235.42 kJ/mol, respectively, implying the oxidation of Hg 0 by Fe(VI) is spontaneous and thorough. Finally, industrial feasibility analysis indicates that Fe(VI) has the practical potential to be a promising removal agent for Hg 0 emission control from coal-fired flue gas, which might be integrated into the existing mainstream flue gas desulfurization scrubber to achieve the removal of multi-pollutants simultaneously, in prospect.